Autophagy-related long non-coding RNA MIR210HG plays a therapeutic role in hepatocellular carcinoma - Chaoqun Zhang; Dianxing Sun; Huifang Zhou; Chao Liu; Jie Ruan; Jiwen Kang; Ying Xie (Discover Oncology)
Abstract Objective This study aimed to investigate the role of the autophagy-related long noncoding RNA (lncRNA) MIR210HG in hepatocellular carcinoma and its potential as a therapeutic target. Methods LncRNA MIR210HG expression and its correlation with survival outcomes in hepatocellular carcinoma patients were analyzed using data from The Cancer Genome Atlas (TCGA). Kaplan–Meier and Cox regression analyses were conducted to assess survival correlations. Quantitative reverse transcription PCR was used to measure lncRNA MIR210HG expression in liver cancer cells and normal liver cells. Functional assays, including CCK-8, Transwell, flow cytometry, and western blot, were performed to evaluate the effects of lncRNA MIR210HG on cell proliferation, invasion, apoptosis, and autophagy in hepatocellular carcinoma. Results Elevated lncRNA MIR210HG expression correlated with poor overall survival in hepatocellular carcinoma patients. LncRNA MIR210HG expression was significantly up-regulated in hepatocellular carcinoma cells compared to normal liver cells. Knockdown of lncRNA MIR210HG inhibited cell proliferation and autophagy, while promoting apoptosis in hepatocellular carcinoma cells, findings that were confirmed through both in vitro and in vivo studies. Conclusion The findings suggest that lncRNA MIR210HG contributes to hepatocellular carcinoma progression by regulating autophagy and could serve as a promising therapeutic target in hepatocellular carcinoma treatment strategies.